Variation in Fluid and Vasopressor Use in Shock With and Without Physiologic Assessment: A Multicenter Observational Study. Issue 10 (October 2020) - Chen, Jen-Ting; Roberts, Russel; Fazzari, Melissa J.; Kashani, Kianoush; Qadir, Nida; Cairns, Charles B.; Mathews, Kusum; Park, Pauline; Khan, Akram; Gilmore, James F.; Brown, Anne Rain T.; Tsuei, Betty; et al.
Abstract : Objectives: To characterize the association between the use of physiologic assessment (central venous pressure, pulmonary artery occlusion pressure, stroke volume variation, pulse pressure variation, passive leg raise test, and critical care ultrasound) with fluid and vasopressor administration 24 hours after shock onset and with in-hospital mortality. Design: Multicenter prospective cohort study between September 2017 and February 2018. Settings: Thirty-four hospitals in the United States and Jordan. Patients: Consecutive adult patients requiring admission to the ICU with systolic blood pressure less than or equal to 90 mm Hg, mean arterial blood pressure less than or equal to 65 mm Hg, or need for vasopressor. Interventions: None. Measurement and Main Results: Of 1, 639 patients enrolled, 39% had physiologic assessments. Use of physiologic assessment was not associated with cumulative fluid administered within 24 hours of shock onset, after accounting for baseline characteristics, etiology and location of shock, ICU types, Acute Physiology and Chronic Health Evaluation III, and hospital (beta coefficient, 0.04; 95% CI, −0.07 to 0.15). In multivariate analysis, the use of physiologic assessment was associated with a higher likelihood of vasopressor use (adjusted odds ratio, 1.98; 95% CI, 1.45−2.71) and higher 24-hour cumulative vasopressor dosing as norepinephrine equivalent (beta coefficient, 0.37; 95% CI, 0.19−0.55). The use of vasopressor was associated with increased odds of in-hospital mortality (adjusted odds ratio, 1.88; 95% CI, 1.27−2.78). In-hospital mortality was not associated with the use of physiologic assessment (adjusted odds ratio, 0.86; 95% CI, 0.63−1.18). Conclusions: The use of physiologic assessment in the 24 hours after shock onset is associated with increased use of vasopressor but not with fluid administration. Abstract : Supplemental Digital Content is available in the text.